Packaged ready-to-eat food consumption status of parents for their children and the factors that affect the consumption: Turkish case - Kücük, Sibel; Uludasdemir, Dilek; Kücük, Mihran (Progress in Nutrition, 2019)
Aim: Consumption of packaged ready-to-eat food is increasing steadily worldwide. Indeed, relevant literature highlights that package food could affect children’s growth and development negatively because of the additive ingredients. Methods: This descriptive research aims to investigate packaged ready-to-eat food consumption status of the parents who had under 18 years old children, and lived in a region where middle and low income families live, and the factors that affect ready-to-eat food consumption. Quantitative data were collected using a questionnaire that consisted of 31 questions. Number, percentage, mean, standard deviation, Chi square tests were used to present findings. Results:The findings showed that although most of the parents expressed that packaged foods were harmful to health, parents kept package foods in their houses and they had a store for the package foods that they called junk food drawer. Parents bought packaged foods for their children for various reasons because of children’s desire, the effect of the trade of the product and the effect of the label of the food. Parents’ age, gender, education and income status and also the number of children parents had affected buying packaged ready-to-eat food and gender, education and income, the number of children parents affect the reason why parents buy packaged ready-to-eat food and participants’ age affected the features considered while buying the packaged ready-to-eat food affect the. Conclusion: Raising awareness among the parents regarding the negative effects of packaged ready-to-eat food is significant, and activities to raise awareness should be disseminated in all units of the society that are concerning children.